Una especie nueva, Castela juyyaania (Simaroubaceae), y tres registros nuevos para la flora semiárida de Sinaloa, México - Juan F. Pío-León; Jesús A. Carrillo-García; Bladimir Salomón-Montijo; Gilberto Márquez-Salazar (Acta Botanica Mexicana)
Resumen